Smartphone usage among university students / Chan Yuen Fook … [et al.] - Fook, Chan Yuen; Narasuman, Suthagar; Abdul Aziz, Norazah; Tau Han, Cheong (Universiti Teknologi MARA, 2021)
Smartphone users have increased to over two and a half billion people and it is predicted to rise to five billion by the year of 2020. Prolonged smartphone usage indicates obsession with the virtual world. As smartphone users include students from secondary school to tertiary levels, their constant engagement with mobile phones raises questions of addiction that may have negative consequences on academic performance. Hence the present study aimed to examine problematic smartphone use, hours spent, factors and activities involved, and argue the possible risks of phone addiction among Malaysian university students. The study employed a descriptive research design to collect data, while data analysis was conducted using descriptive statistics such as mean, standard deviation, frequency and percentage. Fifty-five out of eighty students from a public higher learning institution responded to a survey. The results indicated that most of them somewhat agreed that they used smartphones without any compelling reasons at every hour and that it induced emotional stability. The findings implied that the students were somewhat addicted to smartphones but did not use their smartphones for academic purposes. It is expected that the findings from this study will help higher learning institutions to better understand the patterns of smartphone usage among university students and to reduce or control academically disruptive smartphone addiction behavior.